1994
DOI: 10.1038/371171a0
|View full text |Cite
|
Sign up to set email alerts
|

c-Fos transcriptional activity stimulated by H-Ras-activated protein kinase distinct from JNK and ERK

Abstract: Ras proteins exert their mitogenic and oncogenic effects through activation of downstream protein kinases. An important question is how Ras-generated signals reach the nucleus to activate downstream target genes. AP-1, a heterodimeric complex of Jun and Fos proteins, which activates mitogen-inducible genes, is a major nuclear target of Ras. Ras can stimulate AP-1 activity by inducing c-fos transcription, a process which is probably mediated by the ERK1 and -2 mitogen-activated protein (MAP) kinases, which phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
206
0
6

Year Published

1996
1996
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 325 publications
(217 citation statements)
references
References 38 publications
5
206
0
6
Order By: Relevance
“…Finally, we found that the kinase-inactive JNK1 expression construct countered the stimulation of u-PAR promoter activity by c-Ha-Ras (Figure 9c) with an equimolar amount of the dominant negative plasmid resulting in over 65% inhibition compared with the empty vector (SRa Vector). Taken together, these results suggest that while c-Ha-ras can activate multiple downstream signaling cascades (Deng and Karin 1995;RodriguezViciana et al, 1994;Russell et al, 1995;Kolch et al, 1991), u-PAR promoter activity in OVCAR-3 cells is regulated by this oncogene partly through a JNKdependent signaling module.…”
Section: The Stimulation Of U-par Promoter Activity By the Expressionmentioning
confidence: 81%
“…Finally, we found that the kinase-inactive JNK1 expression construct countered the stimulation of u-PAR promoter activity by c-Ha-Ras (Figure 9c) with an equimolar amount of the dominant negative plasmid resulting in over 65% inhibition compared with the empty vector (SRa Vector). Taken together, these results suggest that while c-Ha-ras can activate multiple downstream signaling cascades (Deng and Karin 1995;RodriguezViciana et al, 1994;Russell et al, 1995;Kolch et al, 1991), u-PAR promoter activity in OVCAR-3 cells is regulated by this oncogene partly through a JNKdependent signaling module.…”
Section: The Stimulation Of U-par Promoter Activity By the Expressionmentioning
confidence: 81%
“…These results suggest that ALK can drive NF-kB activation, and that activation is increased with the presence of IRS-1. In addition, the lack of activation of AP-1, SRE and SRF promoter/reporter constructs indicates that the ALK/ IRS-1-mediated MAPK and PI3-kinase activity does not cause a global increase of transcription of all mitogenesis-and survival-related pathways Deng and Karin, 1994;Minden et al, 1994;Huang et al, 1996) but instead a relatively selective activation of NF-kB in this cellular context. The significance of this activation is supported by the effect of the knockdown of the p65 subunit of NF-kB, which disrupts the transformed phenotype of the 32D/ IRS-1/ALK cells (Figure 7).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, only cells containing both ALK and IRS-1 showed this NF-kB activity (Figure 6b not show any induction in any of the cell lines, although a small but inconsistent activation of the AP-1 promoter/reporter was seen with the 32D/IRS-1 ALK cells (Figure 6a). This lack of AP-1 activity was particularly surprising as control experiments with 32D cells showed that expression of pFC-MEKK, a constitutively active MEKK, induced activation of the AP-1 promoter/ reporter by eightfold (not shown) and AP-1 had been shown by others to be activated by MAPK (Deng and Karin, 1994;Minden et al, 1994) and PI3-kinase (Huang et al, 1996) signaling.…”
Section: Knockdown Of Mk In 32d/irs-1/alkmentioning
confidence: 93%
“…PTX-induced changes in intracellular calcium levels may trigger the activation of kinases, such as the ras/JNK pathway, which could then lead to the activation of cfos and cjun and promote expression of costimulatory molecules and cytokine production [28,29].…”
Section: Discussionmentioning
confidence: 99%